MECHANISM OF ELECTROMAGNETIC INTER-COMMUNICATION IN LIVING ORGANISMS. - Vishvakarma B.R. (My University, 2025)
The author proposes a new hypothesis on the mechanism of some electromagnetic inter-communication between two organisms through significant role of electromagnetic waves. The concept involves only informational function of electromagnetic wave and therefore, the energetic aspect of interaction with biological system is ignored. The electromechanical effects in bone have been shown responsible for such informational activity where it works as a main electromagnetic wave generator along with other minicoherent generators of nerves and muscles. The signal strength is shown to depend on the stress applied though hydrostatic pressure or muscle contraction. The rectification property of membrane is shown responsible for the reception of such biological electromagnetic signal which changes the physiological processes in receiving organism. Thus all such reactions of electromagnetic fields with organism which do not involve sense perception can be compared to some extent with corresponding changes in the physiological processes.